Instability of alloxan-induced diabetes and its impact on sex and thyroid hormones in male wistar rats-a pilot study: DOI: 10.48129/kjs.15291 - Osibemhe, Martin; Orji, Blessing; Omaji, Gloria; Amune, Elizabeth; Ezekiel, John (Kuwait Journal of Science, 2023)
The relationship between diabetes mellitus and sex and/or thyroid hormones has been well documented in both human and animal studies ditto auto-reversibility of alloxan. However, the correlation between unstable diabetes and these hormones have little or no information in literatures; hence, the focus of this study. Diabetes was induced with a single intraperitoneal injection of 150 mg/kg of freshly prepared alloxan. Fifteen Wistar male rats were randomly selected into three groups of five rats per group. One group served as normal control, another group (diabetic rats) served as diabetic control while the last group which served as reversed diabetic contains animals whose blood glucose serendipitously became normoglycemic post-diabetic confirmation. All animals were maintained on normal rat feed and water ad libitum. The animals were monitored for 14 days. Blood glucose was monitored at intervals of 7 days after basal (before diabetes induction) and day 1(diabetes confirmation) values had been noted. Sex hormones: Luteinizing hormone (LH), follicle stimulating hormone (FSH), and estrogen (E) and thyroid hormones: Triiodothyronine (T3), tetraiodothyronine (T4) and thyroid stimulating hormone (TSH) were assayed after 14 days. Alloxan caused alteration in blood glucose levels of both diabetic and reversed diabetic groups. T4 level was lowered significantly in both diabetic (11.32 ± 0.26 μg/ml) and reversed diabetic (11.00 ± 0.16 μg/ml) groups in relation to the control. Other assayed hormones were not different significantly from the control. These findings indicate that diabetes׳ influence on these hormones may not be dependent on glucose gradation. Keywords: Alloxan, diabetes, intraperitoneal, normoglycemic, tetraiodothyronine, triiodothyronine,